Case studies of electrical characterisation of graphene by terahertz time-domain spectroscopy. (17th February 2021) - Whelan, Patrick R; Zhou, Binbin; Bezencenet, Odile; Shivayogimath, Abhay; Mishra, Neeraj; Shen, Qian; Jessen, Bjarke S; Pasternak, Iwona; Mackenzie, David M A; Ji, Jie; Sun, Cunzhi; Seneor, Pierre; et al.
Abstract: Graphene metrology needs to keep up with the fast pace of developments in graphene growth and transfer. Terahertz time-domain spectroscopy (THz-TDS) is a non-contact, fast, and non-destructive characterization technique for mapping the electrical properties of graphene. Here we show several case studies of graphene characterization on a range of different substrates that highlight the versatility of THz-TDS measurements and its relevance for process optimization in graphene production scenarios.